Unpacking the Impact of Family Communication Patterns on Gen Z Professional Performance, Mediated by Work Ethic and Moderated by Organizational Culture - Bambang Septiawan; Zulkarnain Zulkarnain; Nik Haryanti (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study investigates the relationships between family communication patterns, Organizational culture, work ethic, and professional performance within the frameworks of social cognitive theory and theory of planned behavior. Research Method: Employing a quantitative cross-sectional approach, with 311 respondents. The research analyzes data from participants to test six hypotheses by using SEM-PLS and SMART PLS software. Results and Discussion: The results prove that it significantly enhances both work ethic and professional performance, with work ethic as a key mediator. These findings extend prior literature by focusing on subjective performance perceptions, highlighting cultural influences, particularly in collectivist contexts, and challenging traditional models of work-family facilitation. The study's novelty lies in integrating those theories to explain these dynamics, offering fresh insights into how personal and environmental factors shape workplace outcomes. Implications: The results suggest integrating family support and work ethic development into organizational policies to boost employee performance, alongside conflict resolution strategies to manage dual commitments. Originality: The originality of this research lies in the integration of three domains that have previously been studied largely separately, namely Family Communication Patterns (Koerner & Fitzpatrick, 2002; Schrodt et al., 2008), Work Ethic (Miller & Smith, 2019; Weber & Seron, 2019), and Employee Performance (Borman & Motowidlo, 1997) into a single model mediated by organizational culture among Generation Z employees in Indonesia.